KOMPOSISI PROKSIMAT DAN INDEKS GLIKEMIK NIRA AREN - Solang, Margaretha; Ningsih N. Ismail, Yurnia; D. Uno, Wirnangsih (Universitas Jambi, 2020)
This research intended to evaluate the proximate composition and palm juice glycemic index. The analysis of water, protein, and ash contents used the oven, semi-micro Kjeldahl, and thermogravimetry methods, respectively. Meanwhile, fat, carbohydrate, and sugar contents were analyzed by relying on direct extrusion method with a Soxhlet, by difference method , and Luff Schoorl method, respectively. Further, the analysis of the glycemic index employed the calculation of area under the curve using the finger-prick capillary blood method. The measurement of blood glucose levels was done to ten respondents who were given pure glucose and palm juice. The results revealed that palm juice contained 91.1% water, 0.28% ash, 0.41% protein, 0% fat, 8.21% carbohydrate, and 0,67% sugar. The average blood glucose of the respondents after consuming pure glucose and palm juice in minute 0, 30, 60, 90, and 120 arrived at 93.2 mg/dL, 155.4 mg/dL, 124.2 mg/dL, 93.8 mg/dL, 79.1 mg/dL, and 81.8 mg/dL, 118.6 mg/dL, 92.6 mg/dL, 74.1 mg/dL, and 63.7 mg/dL. The value of the palm juice glycemic index was 35.56 (low category), so that this juice could function as an alternative drink to maintain blood glucose levels.